Sudan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper examines the monetary policy framework in Sudan, and assesses the effectiveness of monetary transmission mechanism since the secession of South Sudan. The econometric analysis concludes that reserve money, the exchange rate, and private sector credit are the main determinants of inflation after the secession of South Sudan and that the transmission lags have been shortened significantly compared with previous studies. These findings reinforce the need for a comprehensive package of fiscal and monetary measures that strengthens the monetary policy framework and improves its effectiveness.